Biochemical diagnosis of Cushing's disease: Screening and confirmatory testing. Issue 1 (January 2021) - Petersenn, Stephan
Abstract : Due to the variable clinical features and its rarity diagnosis of Cushing's disease (CD) is often delayed. Clearly, awareness for CD needs to be raised, accompanied by the availability of simple and accurate screening tests. Late-night salivary cortisol (LNSC), 1 mg dexamethasone suppression test (DST), and urinary free cortisol (UFC) have all been extensively studied, demonstrating high sensitivity and specificity for the diagnosis of Cushing's syndrome. However, each of those well-established tests has its own distinctive features, making it preferable in specific clinical conditions and patient groups. To choose the most appropriate test in individual patients, an expert endocrinologist should be consulted. This review will discuss the pitfalls for each of those tests.